CO2‐Saturated Brine Injection Into Unconsolidated Sandstone: Implications for Carbon Geosequestration. Issue 11 (5th November 2019) - Yu, Hongyan; Zhang, Yihuai; Ma, Yao; Lebedev, Maxim; Ahmed, Shakil; Li, Xiaolong; Verrall, Michael; Squelch, Andrew; Iglauer, Stefan
Abstract: Carbon dioxide (CO2 ) injection into deep depleted hydrocarbon reservoirs or saline aquifers is currently considered the best approach to large‐scale CO2 storage. Importantly, the pore structure and permeability of the storage rock are affected by fines release, migration, and reattachment in the initial stage of CO2 injection, especially in unconsolidated sandstone reservoirs. It is thus necessary to better understand the pore structure changes and the associated permeability evolution during and after CO2 injection. We thus imaged an unconsolidated sandstone at reservoir conditions before and after CO2 ‐saturated brine ("live brine") injection in situ via X‐ray microcomputed tomography to explore the effects of fines migration and mineral dissolution induced by CO2 injection. We found that in the examined sample, large pores dominated the total porosity, and porosity slightly increased after live‐brine flooding. Moreover, and importantly, the pore structure changed significantly: large pores were further enlarged while small pores shrank or even disappeared. These structural changes in the tested sample were caused by mobilized fines due to the high‐fluid interstitial velocity, which eventually reattached to the grains further downstream. Furthermore, the impact of the pore structural changes on permeability were analyzed in detail numerically. These permeability results are consistent with a fines migration mechanism where reattached fines block pore throats and thus decrease permeability drastically. We therefore can conclude that live brine injected into the examined unconsolidated sandstone will slightly improve storage space (porosity slightly increased); however, injectivity may be severely impaired by the permeability reduction. Key Points: The large pores in the examined unconsolidated sandstone dominated the total porosity, and porosity slightly increased after live‐brine flooding The pore structure of the examined unconsolidated sandstone changed significantly, caused by fines migration during live‐brine injection The examined sample's permeability drastically decreased due to reattached fines that blocked the pore throats